Experience of Grade III Students in Implementing the Caring Code in Nursing Study Program - Karo, Mestiana Br.; Tampubolon, Lindawati Farida; Silalahi, Susta Maria (GLOBAL HEALTH SCIENCE GROUP, 2024)
Caring code is a guideline for how to implement good caring behavior. Students are the embryo of future leaders. Caring is one of the most important aspects of nursing while prospective nurses are studying nursing education, where teaching and instilling caring attitudes and behavior is very important so that it becomes their lifestyle so that they can be more confident, care more about others, and always give their best. for others. The aim of this research is to determine the experiences of grade III students in implementing the caring code at the STIKes Santa Elisabeth Medan nursing study program in 2023. This research uses a qualitative approach with phenomenological methods. Data collection was carried out using in-depth interviews with 9 questions. Participants were taken using the data saturation principle of 5 participants. The data analysis technique used is thematic analysis. The author collects data from respondents, first separating the completeness of participant statements 1 - 5Then the author wrote down the participant's statements in the form of a research transcript while adjusting the transcript with the recording results.Next, the author reads the interview transcript and quotes meaningful statements from all participants while giving color. The author tries to find the meaning of these key statements to form them into a category, the author tries to analyze and look for relationships between categories to find meaning/content and finally the author then brings together similar categories and groups them into a theme. Based on the results of direct interviews, the research results were obtained: Caring code is respecting fellow students. Caring code is providing wholehearted service to fellow students. Caring code is paying attention to students. Caring code is a student's sensitivity. Caring code is cooperation with students.